2000
DOI: 10.1177/089033440001600313
|View full text |Cite
|
Sign up to set email alerts
|

Beta Blockers and Lactation: An Update

Abstract: Beta-adrenergic antagonists are one of the most commonly used class of agents in the treatment of hypertension. They have also demonstrated utility in the treatment of angina pectoris and certain arrhythmias and for the reduction in mortality following a myocardial infarction. The use of this class of agents creates the potential for beta-blocker exposure among lactating women. This review focuses on the most up-to-date data regarding the more common agents--metoprolol, atenolol, propranolol, carvedilol, nadol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…1). Shannon et al [20] reported the excretion of several beta blockers into breast milk. The authors reported that, on an average, milk- Table 3 Pharmacokinetic parameters of pindolol enantiomers in parturient women (n = 6) treated with multiple doses of racemic pindolol ( to-serum concentrations ranged from 3.0 to 3.5 for metoprolol, 4.6 for sotalol, 2.7 for nadolol, from 2.0 to 11.6 for betaxolol, 2.0 for propranolol, and from 1.1 to 3.1 for atenolol.…”
Section: Resultsmentioning
confidence: 99%
“…1). Shannon et al [20] reported the excretion of several beta blockers into breast milk. The authors reported that, on an average, milk- Table 3 Pharmacokinetic parameters of pindolol enantiomers in parturient women (n = 6) treated with multiple doses of racemic pindolol ( to-serum concentrations ranged from 3.0 to 3.5 for metoprolol, 4.6 for sotalol, 2.7 for nadolol, from 2.0 to 11.6 for betaxolol, 2.0 for propranolol, and from 1.1 to 3.1 for atenolol.…”
Section: Resultsmentioning
confidence: 99%
“…115,116 Although symptoms caused by β-blockade (such as brady cardia and hypoglycaemia) have not previously been reported following exposure to propranolol or metoprolol via milk, some authors nevertheless recommend that exposed infants should be closely observed for these signs. 117 Even though such effects perhaps could be an issue in preterm infants or newborns, we consider it unlikely that any such pharmacological effect would arise in a breastfed infant.…”
Section: Ergot Alkaloidsmentioning
confidence: 93%
“…[34] β-blockers are suggested as first-choice medications during lactation if migraine prophylaxis is considered. [41] Propranolol is excreted into breast milk, but the amounts are considerably lower. Although symptoms caused by β-blockade (such as bradycardia and hypoglycaemia) have not previously been reported following exposure to propranolol or metoprolol via milk, some authors nevertheless recommend that exposed infants should be closely observed for these signs.…”
Section: β-Blockersmentioning
confidence: 99%